Bile acid malabsorption assessed by 7 alpha-hydroxy-4-cholesten-3-one in pediatric inflammatory bowel disease: Correlation to clinical and laboratory findings. (1st September 2014) - Gothe, F.; Beigel, F.; Rust, C.; Hajji, M.; Koletzko, S.; Freudenberg, F.
Abstract: Background and aims: Measurement of 7 alpha-hydroxy-4-cholesten-3-one (C4) in serum is a semiquantitative test for bile acid malabsorption (BAM). We have previously established pediatric normal values for C4 with an upper limit of normal of 66.5 ng/mL, independent of age and sex. Here we performed the C4 test in 58 pediatric patients with Crohn's disease (CD) and ulcerative colitis (UC). Methods: C4 was measured using high performance liquid chromatography (HPLC) in fasting serum samples of 44 patients with CD (range 7–19 years) and 14 with UC (4–18 years). Disease activity was assessed by the pediatric CD and UC activity indices (PCDAI and PUCAI, respectively) plus serum (CRP, ESR) and fecal inflammatory markers (calprotectin). Results: C4 concentrations were increased in 10 CD (23%) (range: 70.8–269.3 ng/mL) but only one UC patient (72.9 ng/mL). CD patients with diarrhea (n = 12) had higher C4-values compared to those without (76.9 vs. 30.4 ng/mL; p = 0.0043). Ileal resection in CD patients (n = 10) was associated with increased C4 concentrations (81.2 vs. 24.3 ng/mL, p = 0.0004). No correlation was found between C4 values and inflammatory markers. Six of 7 CD patients with persistent diarrhea but quiescent disease (PCDAI ≤ 12.5) had C4 values indicating BAM. Conclusion: Elevated C4 concentrations indicating BAM are common in children with CD. They are associated with ileal resection and non-bloody diarrhea in the absence of active disease or elevated inflammatory markers. The C4-test identifies a subgroup of CD patients with persistent diarrhea in spite of clinical remission which may benefit from bile acid binding therapy.